The Birth of Paleomagnetism in Latin America: Argentina - Vilas, Juan Francisco A. (2013)
Paleomagnetic activities in Latin America started with the first field trip of the young Ken Creer in 1957. In the early sixties, and by initiative of the by then Director of the Department of Geological Sciences at the University of Buenos Aires, Feliz Gonzalez Bonorino; the engineer Daniel A. Valencio is hired to start the teaching of Geophysics to the undergraduate students of Geology and to begin with the Paleomagnetic research in Argentina. The Paleomagnetic Laboratory of Buenos Aires was created in 1964 and rapidly became an internationally recognized center, promoter of research in the emergent theory of Plate Tectonics and a spreading center of Paleomagnetism in Latin America. The network of friends across the continent and the unselfish cooperation among colleagues from different Latin American countries helped in building up the first laboratories in Brazil and Mexico. Despite several vicissitudes that conspired against its survival along the last five decades, the Paleomagnetic Laboratory “Daniel A. Valencio” continues in full activity honoring the tradition of unselfish and friendly collaboration that shaped its beginnings.